Предмет: Алгебра, автор: mitalodronat44

Того кто решит все кину лечшее ^-^

Приложения:

Ответы

Автор ответа: CVita
1
x^2+7x+6=0 \\ D=b^2-4ac=7^2-4*1*6=49-24=25 \\ x_1_,_2= \frac{-b+_- \sqrt{D}}{2a}  \\ x_1= \frac{-7- \sqrt{25}}{2*1}=-6 \\ x_2= \frac{-7+ \sqrt{25}}{2*1}=-1

(x-2)^2=3x-8 \\ x^2-4x+4=3x-8 \\ x^2-4x+4-3x+8=0 \\ x^2-7x+12=0 \\ D=b^2-4ac=(-7)^2-4*1*12=49-48=1 \\ x_1= \frac{7- \sqrt{1} }{2*1}=3 \\ x_2= \frac{7+ \sqrt{1} }{2*1}=4

6x(2x+1)=5x+1 \\ 12x^2+6x=5x+1 \\ 12x^2+6x-5x-1=0 \\ 12x^2+x-1=0 \\ D=1^2-4*12*(-1)=49 \\ x_1= \frac{-1- \sqrt{49} }{2*12}=- \frac{1}{3}  \\ x_2= \frac{-1+ \sqrt{49} }{2*12}= \frac{1}{4}

( \frac{x}{y}- \frac{y}{x})* \frac{5xy}{x-y}= \frac{x^2-y^2}{yx}* \frac{5xy}{x-y}= \frac{(x-y)(x+y)}{yx}* \frac{5xy}{x-y}=5x+5y
Похожие вопросы